Reciprocity and the feast of San Juan in Otavalo - Barlett, Peggy F. (1988)
The festival of San Juan held in the Otavalo Valley, Ecuador, is the high point of the annual indigenous festivals. Such an event is characterized by meals, ingestion of alcohol, dances and music. It attracts Otavalenos from all parts of Ecuador to their native communities for the purpose of celebration. However, drunkenness and violence, which also characterize these celebrations, have been the source of much criticism. Government emissaries and Catholic and Protestant missionaries have tried to eradicate the party altogether, or at least the drinking custom.